Review of Electron Beam Welding Technology in Space Environment - Liu, Xiaomeng; Dong, Quanlin; Wang, Pengfei; Chen, He (Optik (Stuttgart), 2021)
Electron beam welding (EBW) has many advantages as a space environment welding technology. EBW is suitable for vacuum operations. It can ensure the quality of aerospace material welding joints, high energy efficiency, and maximum penetration depth regardless of the material type and surface conditions. It has been tested successfully many times in actual space environments. The effects of the space environment on the welding technology are analyzed from the aspects of microgravity, vacuum conditions, and temperature differences in this article. The research directions of space welding technology, the principles, and the structure and development course of vacuum electron beam welding are also expounded. The development of space electron beam gun technology in the United States and former USSR has been reviewed in detail, and the two typical structures and characteristics have been analyzed. This review can provide reference for the design of new space electron beam guns.